Process‐relevant concentrations of the leachable bDtBPP impact negatively on CHO cell production characteristics. (4th September 2016) - Kelly, Paul S.; McSweeney, Shane; Coleman, Orla; Carillo, Sara; Henry, Michael; Chandran, Deepak; Kellett, Andrew; Bones, Jonathan; Clynes, Martin; Meleady, Paula; Barron, Niall
Abstract : The biopharmaceutical industry has invested considerably in the implementation of single‐use disposable bioreactors in place of or in addition to their stainless steel‐counterparts. This new wave of construction materials for disposable bioprocess containers encompass a plethora of uncharacterized secondary compounds that, when in contact with the culture media, can leach, contaminating the bioprocess. One such cytotoxic leachable already receiving attention is bis(2, 4‐ di‐tert‐ butylphenyl)‐phosphate (bDtBPP), a breakdown product of the secondary antioxidant Irgafos 168 in polyethylene‐film based bags. This compound has been demonstrated to inhibit cell growth at concentrations ranging from 0.12 to 0.73 mg/L across an array of cell lines. Here we demonstrate that a further two CHO cell lines exhibit sensitivity to bDtBPP exposure at concentrations lower than that previously reported (0.035–0.1 mg/L). Furthermore, these inhibitory concentrations reflect bDtBPP levels found to leach early into the bioprocess, exposing reactor inoculums to serious risk. Quantitative label‐free LC‐MS/MS revealed that irrespective of cell line or concentration of bDtBPP, 8 proteins were found to be commonly differentially expressed in response to exposure to the compound highlighting biological processes related to cellular stress. Although the glycoprofile of the recombinant antibody remains primarily unchanged, we demonstrate that this compound when spiked at meaningful concentrations 72 h into culture considerably reduces the maximum cell density achieved. Studies like this reinforce the requirement for the complete characterization of all potential leachable compounds from disposable materials to assess their risk not only to the patient but also to the production pipeline itself. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1547–1558, 2016